Valores hematológicos de referência para papagaios- verdadeiros (Amazona aestiva - Psittacidae) mantidos em cativeiro. - Carlos Eduardo Silveira Goulart (2006)
The present work aimed to describing values and aspects that can serve as parameters of physiological reference for the hematology of the blue-fronted-parrot (Amazona aestiva - Psittacidae), as well as determining the occurrence of hemoparasites, in an established commercial breeder in Betim - Minas Gerais, Brazil. Fifty eight blue-fronted-parrot (Amazona aestiva) on captivity for at least three years, adults, of both sex and in adequate conditions of health were used. After an statistics analysis of the results, the following basic parameters were found (Mean + Standard Derivation): Erythrocytes (x106/mm3): 2,54 + 0,45; Hemoglobin (g/dL): 16,28 + 1,13; Hematocrit (%): 44,66 + 4,45; Mean corpuscular volume (µ3ou fL): 179,99 + 32,15; Mean corpuscular hemoglobin (µµg ou pg): 65,50 + 8,15; Mean corpuscular hemoglobin concentration (g/dL or %): 36.51 + 2,90; immature erythrocytes (x103/mm3): 32,06 + 1,85; Thrombocytes (x 103/mm3): 16,61 + 7,45; Leukocytes (x 103/mm3): 7,01 + 4,15; Heterphils (x 103/mm3): 3,40 + 2,05; Lymphocytes (x 103/mm3): 3,37 + 2,83; Monocytes (x 103/mm3): 0,16 + 0,16; Basophils (x 103/mm3): 0,08 + 0,09; Eosinophils (x103/mm3): 0,02 + 0,05; immature granulocytes (x /mm3): 37,95 + 84,17. Parameters for subpopulations of immature erythrocytes and immature granulocytes in the peripheral blood, as well as morphologic characteristics of the subpopulations of leukocytes and thrombocytes were also evaluated. The occurrence of Plasmodium sp. in peripheral blood occurred in 29,31% of birds, and the parasitemy was 0,031% + 0,031%. Significant differences had not been observed between: sex; clinical and reproductive parameters. There was no statistical difference on hematological parameters between both groups (with or without Plasmodium sp.), except for the parameters of counting of juvenile polychromatic erythrocytes and advanced polychromatic erythrocytes (P = 0,004 and 0,025 respectively).